Question and Answers Forum

All Questions      Topic List

Differentiation Questions

Previous in All Question      Next in All Question      

Previous in Differentiation      Next in Differentiation      

Question Number 93064 by  M±th+et+s last updated on 10/May/20

prove that   (d/dx)x^n =nx^(n−1)

provethatddxxn=nxn1

Commented by mr W last updated on 10/May/20

(d/dx)x^n   =lim_(Δx→0) (((x+Δx)^n −x^n )/(Δx))  =lim_(Δx→0) ((x^n (1+((Δx)/x))^n −x^n )/(Δx))  =lim_(Δx→0) ((x^n [1+n(((Δx)/x))+((n(n−1))/(2!))(((Δx)/x))^2 +((n(n−1)(n−2))/(3!))(((Δx)/x))^3 +...]−x^n )/(Δx))  =lim_(Δx→0) x^n [n((1/x))+((n(n−1))/(2!))×((Δx)/x^2 )+((n(n−1)(n−2))/(3!))×(((Δx)^2 )/x^3 )+...]  =x^n n((1/x))  =nx^(n−1)

ddxxn=limΔx0(x+Δx)nxnΔx=limΔx0xn(1+Δxx)nxnΔx=limΔx0xn[1+n(Δxx)+n(n1)2!(Δxx)2+n(n1)(n2)3!(Δxx)3+...]xnΔx=limΔx0xn[n(1x)+n(n1)2!×Δxx2+n(n1)(n2)3!×(Δx)2x3+...]=xnn(1x)=nxn1

Commented by  M±th+et+s last updated on 10/May/20

thank you sir

thankyousir

Commented by mathmax by abdo last updated on 10/May/20

let f(x)=x^n   we have f^′ (x)=lim_(h→0)   ((f(x+h)−f(x))/h)  =lim_(h→0)   (((x+h)^n −x^n )/h) =lim_(h→0) (((x+h−x)((x+h)^(n−1)  +(x+h)^(n−2) x+....(x+h)x^(n−2) +x^(n−1) )/h)  =lim_(h→0)    (x+h)^(n−1)  +(x+h)^(n−2) x +....+(x+h)x^(n−2)  +x^(n−1)   =x^(n−1)  +x^(n−1) +...+x^(n−1)  (n time) =nx^(n−1)   ⇒  f^′ (x) =nx^(n−1)

letf(x)=xnwehavef(x)=limh0f(x+h)f(x)h=limh0(x+h)nxnh=limh0(x+hx)((x+h)n1+(x+h)n2x+....(x+h)xn2+xn1h=limh0(x+h)n1+(x+h)n2x+....+(x+h)xn2+xn1=xn1+xn1+...+xn1(ntime)=nxn1f(x)=nxn1

Commented by  M±th+et+s last updated on 10/May/20

nice work.  thank you sir

nicework.thankyousir

Commented by arcana last updated on 10/May/20

b  the correct way to prove it is for  induction  ∗ prove it for the first cases.  ∗assume that is true, then prove the  case n+1.

bthecorrectwaytoproveitisforinductionproveitforthefirstcases.assumethatistrue,thenprovethecasen+1.

Commented by mathmax by abdo last updated on 11/May/20

you are welcome.

youarewelcome.

Commented by Rio Michael last updated on 11/May/20

correct sir, but the method used above can  also be used since the question didnt specify by induction.

correctsir,butthemethodusedabovecanalsobeusedsincethequestiondidntspecifybyinduction.

Answered by Rio Michael last updated on 11/May/20

by mathematic induction,  prove for n = 0 : (d/dx)(x^0 )  = 0 and n = 0 into nx^(n−1)  = 0  prove for n = 1 , LHS = (d/dx)(x) = 1                                     RHS = 1(x)^(1−1)  = 1  ⇒ the derivative formula is true for n=0,1  assume it is true for n = k  ⇒ (d/dx) x^k  = kx^(k−1)   prove for n = k +1    (d/dx)(x)^(k+1)  = (d/dx)(x^k  × x) = x^k  +  x(d/dx)(x^k )                                                    = x^k  + x(kx^(k−1) )                                                    = x^k  + kx^k                                                     = (k+1)x^k   hence the derivatve formula is true for n = k+1  hence ∀ n ∈Z , (d/dx)x^n  = nx^(n−1) .

bymathematicinduction,proveforn=0:ddx(x0)=0andn=0intonxn1=0proveforn=1,LHS=ddx(x)=1RHS=1(x)11=1thederivativeformulaistrueforn=0,1assumeitistrueforn=kddxxk=kxk1proveforn=k+1ddx(x)k+1=ddx(xk×x)=xk+xddx(xk)=xk+x(kxk1)=xk+kxk=(k+1)xkhencethederivatveformulaistrueforn=k+1hencenZ,ddxxn=nxn1.

Commented by  M±th+et+s last updated on 11/May/20

nice work.  thanx

nicework.thanx

Terms of Service

Privacy Policy

Contact: info@tinkutara.com